POR Nível: Construção e validação de um teste de colocação para o Português Língua Estrangeira – resultados de um estudo-piloto - Gramacho, Carolina; Madeira, Ana; Martins, Cláudia; Alexandre, Nélia; Pinto, Jorge; Correia, Susana (Revista da Associação Portuguesa de Linguística, 2019)
Placement tests are a form of assessment that aims at placing students in appropriate levels. Placement tests must, therefore, be based on validity and reliability arguments to ensure appropriateness and consistency of assessment. Despite the growing interest in Portuguese as a Foreign Language (PFL), both nationally and internationally, to our knowledge there is no validated placement test that informs on general language abilities of adult PFL learners across levels. The POR Nível project aims at designing and validating a placement test for PFL adult learners, from A1 to C1 CEFR levels in grammar, vocabulary, listening and reading components. Corpora of written productions of 15 learners of 3 native languages (English, Mandarin and Spanish) from certified exams of PFL provide the empirical basis for items construction. Also, items’ specifications follow national and international guidelines (CEFR, Camões Profile for PFL), validity, reliability and practicality requirements, and also ALTE and ILTA recommendations. The results found thus far will provide empirical ground for item specification in a validated placement test and eventually contribute to the discussion of the contents of PFL teaching programs.